Visitors’ background as a factor in geosite evaluation. The case of Cenozoic volcanic sites in the Pogórze Kaczawskie region, SW Poland - Różycka, Milena; Migoń, Piotr (Geotourism/Geoturystyka, 2017)
The paper presents a new approach to geosite assessment in which individual preferences and needs of visitors with different backgrounds, i.e. knowledge of Earth science and interest in geoheritage, are taken into account. The aim of the study is to analyze how perspectives of visitors, split into three different categories (viz. geo-expert, interested visitor and unaware visitor), may affect evaluation of geosites. Parallel evaluations of a group of 11 geosites in the Pogórze Kaczawskie region representing mid-Cenozoic volcanism have been carried out and their results compared. Emphasis on different criteria resulted in considerable changes in the positions of certain geosites in the rankings. Based on the assumption that attractiveness of a geosite may be also perceived variously depending on the season, the attempt has been made to include ‘seasonal factor’, i.e. the role of vegetation that obscures the visibility of geological and geomorphological features, in the assessment procedure. Shifts in position of individual geosites were generally minor but this may be related to a small sample used in this pilot study.